Produce an Analytical Map for the Distribution of Air Pollution by Toxic Gases in Baghdad City by Geographic Information System - Hassan, Wassan A (Al-Nahrain Journal of Science, 2018)
Iraq suffers from pollution of the air with many gases, such as carbon dioxide, carbon monoxide, methane, ozone and others. Baghdad governorate was used as an example to measure the amount of air pollution and distribution in the areas of Baghdad and used data for three measurement stations in Baghdad is the station Jadiriya, Andulos and Alwaziriya, which are available only and for three gases are carbon dioxide and carbon monoxide and ozone and 2011 and 2012 and for all months. The study used three methods of mathematical induction (IDW, Kriging and Spline), one of the methods of mathematical induction in GIS programs. Analytical maps of the distribution and distribution of gases were obtained in Baghdad and it became clear that the IDW method is the most accurate of the three methods.